Fluorofenidone alleviates cigarette smoke exposure-induced chronic lung injury by targeting ferroptosis - Yuan Wu; Binbin Li; Yixuan Xuan; Yu Jiang; Jinping Chen; Hong Liao; Jihua Feng; Jianfeng Zhang (Scientific Reports)
Abstract Chronic obstructive pulmonary disease (COPD) is a common condition that poses significant health risks to humans. Pulmonary interstitial fibrosis (PIF) often manifests in advanced stages of COPD. Fluorofenidone (AKF) has a wide range of pharmacological effects, including anti-fibrotic, antioxidant, and anti-inflammatory effects. Therefore, this study aimed to assess the role of AKF in lung injury and its underlying mechanisms. The COPD mice model was constructed by cigarette smoke (CS) combined with lipopolysaccharide (LPS) treatment. The effect of AKF on COPD mice was evaluated by lung injury, lipid peroxidation, inflammatory factors, and the expression of ferroptosis markers. Furthermore, the normal human bronchial epithelial cell line, Beas-2B, was used to verify the mechanism underlying the association between ferroptosis and inflammation. AKF attenuated the cigarette smoke (CS)/LPS-induced inflammatory response in the mouse lungs. Additionally, AKF attenuated the CS/LPS-induced fibrosis response in the mouse lungs. AKF inhibits ferroptosis in lung tissues of CS/LPS-exposed mice. Furthermore, AKF suppressed the inflammatory response and ferroptosis in CSE-treated BEAS-2B cells via NF-κB signaling pathway. AKF can function as a novel ferroptosis inhibitor by inhibiting NF-κB to inhibit airway inflammation and fibrosis, providing a scientific basis for the use of AKF to prevent the progression of COPD and pulmonary fibrosis.